2021
DOI: 10.1186/s12966-021-01193-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a three-armed randomised controlled trial using self-monitoring of daily steps with and without counselling in prediabetes and type 2 diabetes—the Sophia Step Study

Abstract: Background This aimed to evaluate the effects of self-monitoring of daily steps with or without counselling support on HbA1c, other cardiometabolic risk factors and objectively measured physical activity (PA) during a 2-year intervention in a population with prediabetes or type 2 diabetes. Methods The Sophia Step Study was a three-armed parallel randomised controlled trial. Participants with prediabetes or type 2 diabetes were recruited in a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
4
8
1
1
Order By: Relevance
“…Intervention group allocation was not predictive of profile group membership in this study, which contradicts the findings from the study of the effects of the intervention [ 22 ]. Thus, the findings of this study highlight that factors other than the intervention were more important for the PA pattern.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intervention group allocation was not predictive of profile group membership in this study, which contradicts the findings from the study of the effects of the intervention [ 22 ]. Thus, the findings of this study highlight that factors other than the intervention were more important for the PA pattern.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies, we reported the effects of the Sophia Step Study, an RCT using pedometers and counselling as tools to promote PA in diabetes care [ 21 , 22 ]. The results revealed an intervention effect on the maintenance of moderate to vigorous PA (MVPA) but a weak effect on daily steps [ 22 ]. This current study applies secondary analyses to further explore changes in PA behaviour across all participants.…”
Section: Introductionmentioning
confidence: 99%
“…However, apart from our long-term RCT design, we were unable to examine the short-term effects, because we did not measure body composition nor cardiometabolic outcomes during the intervention. Due to lack of changes in physical activity behavior and especially in the levels of moderate-to-vigorous physical activity over 12 months, our findings are in line with 2-years pedometer-based intervention in which no significant increase in daily steps nor improved metabolic health was observed ( Rossen et al, 2021 ). It is likely that changes in moderate-to-vigorous physical activity are needed to have more marked changes in metabolic health.…”
Section: Discussionsupporting
confidence: 84%
“…Consumer-wearable activity trackers have also been found to increase physical activity and to be associated with improvements in cardiometabolic health, including waist circumference, systolic blood pressure, and low-density lipoprotein cholesterol concentration in middle-aged and older patients with chronic diseases ( Franssen et al, 2020 ). A 2-years pedometer-based intervention prevented decrease in daily steps but did not improve cardiometabolic health in over 60 years old patients with prediabetes or type 2 diabetes ( Rossen et al, 2021 ). However, the long-term effects of activity tracker based physical activity interventions on cardiometabolic health outcomes among older adults are still unknown ( Coughlin and Stewart, 2016 ; Stockwell et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, accurate measurement of physical activity (PA) levels has always been a challenge in research aimed to tailor further intervention for at-risk populations [ 4 , 5 ]. Although objective measurement of accelerometer, a motion sensor which has been proved to be comparable to the “gold standard”—doubly labelled water (DLW) method [ 4 , 5 , 6 , 7 , 8 ], has been used in some epidemiological studies recently [ 9 , 10 , 11 ]. Due to the high cost and time-consuming nature of accelerometers, subjective measurements such as questionnaires and PA logs (PAL) [ 12 ], remain the most feasible solution in large-scale population studies [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%